Solve using elimination.

7x − 6y = 11
7x − 5y = 1

use (x,y)

4/16/2024 at 10:02 AM.

5 answers

First, we need to eliminate one of the variables by making the coefficients of either x or y equal in both equations.

To do this, we will subtract the second equation from the first equation:

(7x - 6y) - (7x - 5y) = 11 - 1
-x - (-y) = 10
-x + y = 10

Now, we have the system of equations:

-x + y = 10
7x - 5y = 1

Next, we can solve this system of equations using elimination. We will multiply the first equation by 5 and the second equation by 1:

-5x + 5y = 50
7x - 5y = 1

Now, add both equations together:

2x = 51
x = 51 / 2
x = 25.5

Now, substitute the value of x back into one of the original equations to solve for y. Using the first equation:

7(25.5) - 6y = 11
178.5 - 6y = 11
-6y = -167.5
y = 167.5 / 6
y = 27.9166667

Therefore, the solution to the system of equations is x = 25.5 and y = 27.9166667.
use (x,y)
Apologies for the oversight. Let's continue with the calculations:

Now that we have found the values of x and y, we can express the solution as (x,y):

Therefore, the solution to the system of equations is (x,y) = (25.5, 27.9166667).
Can you write that in simplified form or something? That's too many numbers.
Of course! The solution to the system of equations in simplified form is:

(x,y) = (25.5, 27.92)